Asksia AI LOGO

Sia

Question
Math
Posted 7 months ago

For any real number a the differential equation is given y(t)+ay(t)+9y(t)=0y^{\prime \prime}(t)+a y^{\prime}(t)+9 y(t)=0.
a) Determine for a=10\mathrm{a}=10 the complete solution to the differential equation. b) Determine whether there are values of the number a for which y(t)=2te3ty(t)=2 t e^{\wedge}-3 t is a solution to the differential equation, and if so, state these values of the number a.
Sign in to unlock the answer
Answer from Sia
Posted 7 months ago
Solution by Steps
step 1
Given the differential equation y(t)+ay(t)+9y(t)=0y''(t) + a y'(t) + 9 y(t) = 0, we need to determine the complete solution for a=10a = 10
step 2
Substitute a=10a = 10 into the differential equation: y(t)+10y(t)+9y(t)=0y''(t) + 10 y'(t) + 9 y(t) = 0
step 3
The characteristic equation for this differential equation is r2+10r+9=0r^2 + 10r + 9 = 0
step 4
Solve the characteristic equation: r=10±10241921=10±100362=10±642=10±82r = \frac{-10 \pm \sqrt{10^2 - 4 \cdot 1 \cdot 9}}{2 \cdot 1} = \frac{-10 \pm \sqrt{100 - 36}}{2} = \frac{-10 \pm \sqrt{64}}{2} = \frac{-10 \pm 8}{2}
step 5
This gives us the roots r1=1r_1 = -1 and r2=9r_2 = -9
step 6
The general solution to the differential equation is y(t)=C1et+C2e9ty(t) = C_1 e^{-t} + C_2 e^{-9t}
step 7
To determine if y(t)=2te3ty(t) = 2t e^{-3t} is a solution for some value of aa, substitute y(t)=2te3ty(t) = 2t e^{-3t} into the differential equation y(t)+ay(t)+9y(t)=0y''(t) + a y'(t) + 9 y(t) = 0
step 8
Compute the first derivative: y(t)=2e3t6te3ty'(t) = 2 e^{-3t} - 6t e^{-3t}
step 9
Compute the second derivative: y(t)=6e3t+18te3ty''(t) = -6 e^{-3t} + 18t e^{-3t}
step 10
Substitute y(t)y(t), y(t)y'(t), and y(t)y''(t) into the differential equation: (6e3t+18te3t)+a(2e3t6te3t)+9(2te3t)=0(-6 e^{-3t} + 18t e^{-3t}) + a (2 e^{-3t} - 6t e^{-3t}) + 9 (2t e^{-3t}) = 0
step 11
Simplify the equation: 6e3t+18te3t+2ae3t6ate3t+18te3t=0-6 e^{-3t} + 18t e^{-3t} + 2a e^{-3t} - 6a t e^{-3t} + 18t e^{-3t} = 0
step 12
Combine like terms: (6+2a)e3t+(186a+18)te3t=0(-6 + 2a) e^{-3t} + (18 - 6a + 18) t e^{-3t} = 0
step 13
For the equation to hold for all tt, the coefficients of e3te^{-3t} and te3tt e^{-3t} must be zero: 6+2a=0-6 + 2a = 0 and 186a+18=018 - 6a + 18 = 0
step 14
Solve for aa: 2a=6a=32a = 6 \Rightarrow a = 3
step 15
Therefore, y(t)=2te3ty(t) = 2t e^{-3t} is a solution to the differential equation for a=3a = 3
Answer
The complete solution for a=10a = 10 is y(t)=C1et+C2e9ty(t) = C_1 e^{-t} + C_2 e^{-9t}. The function y(t)=2te3ty(t) = 2t e^{-3t} is a solution to the differential equation for a=3a = 3.
Key Concept
Solving differential equations using characteristic equations and verifying solutions.
Explanation
The characteristic equation helps find the general solution to a linear differential equation. Verifying a specific solution involves substituting it back into the original equation and solving for the parameter.

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Unlock Smarter Learning with AskSia Super!

Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.

30% higher accuracy than GPT-4o
Entire learning journey support
The most student-friendly features
Study Other Question